2018
DOI: 10.1096/fj.201700762r
|View full text |Cite
|
Sign up to set email alerts
|

Deformability of breast cancer cells in correlation with surface markers and cell rolling

Abstract: Although the cancer stem cell (CSC) hypothesis has been around for many years, the reliability of cell-surface markers to classify CSCs has remained debatable. The finding that cancerous cells are significantly more deformable than healthy ones has provided motivation to consider mechanical properties as a possible biomarker for stemness. In this study, using the micropipette aspiration technique, mechanical properties of multiple breast cancer cell lines were investigated and correlated with breast cancer ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 58 publications
(80 reference statements)
1
24
0
Order By: Relevance
“…CD44 is of particular interest, as it is widely expressed in the tumor cells of breast carcinomas [21] and has been shown to promote tumor growth and mediate drug resistance by maintaining cancer stem cell populations [27][28][29]. Therefore, CD44 gene expression was confirmed in Hs578T and MDA-MB-231 cells by qRT-PCR, as demonstrated by others [30][31][32][33] (Figure S2B). CD44 protein expression was then examined by flow cytometry, which demonstrated that CD44 was expressed on the surface of Hs578T and MDA-MB-231 cells (Figure S2C).…”
Section: Cd44 Deletion In Breast Cancer Cell Lines Decreases Expression Of Genes Involved In Cellular Adhesion and Cytokine Activitymentioning
confidence: 70%
“…CD44 is of particular interest, as it is widely expressed in the tumor cells of breast carcinomas [21] and has been shown to promote tumor growth and mediate drug resistance by maintaining cancer stem cell populations [27][28][29]. Therefore, CD44 gene expression was confirmed in Hs578T and MDA-MB-231 cells by qRT-PCR, as demonstrated by others [30][31][32][33] (Figure S2B). CD44 protein expression was then examined by flow cytometry, which demonstrated that CD44 was expressed on the surface of Hs578T and MDA-MB-231 cells (Figure S2C).…”
Section: Cd44 Deletion In Breast Cancer Cell Lines Decreases Expression Of Genes Involved In Cellular Adhesion and Cytokine Activitymentioning
confidence: 70%
“…CSCs exhibit a less adhesive strength towards the basement membrane and hence can be mechanistically enriched from a majority of other cancer cells before being definitively validated by surface marker analysis [22]. Biomechanical profiling of CSCs of different cancers (ovarian, breast, hepatic) using atomic force microscopy or rheological technique like micropipette aspiration has demonstrated that these cells are significantly softer and highly deformable than non-malignant, intermediates and even aggressive late-stage cancer cells [23][24][25]. The soft phenotype has also been shown to be sensitive to the anti-cancer agents [23].…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…It has been demonstrated that breast cancer cells showing the stem-like CD44 + /CD24 − /ALDH1 + phenotype were significantly more deformable than non-CSCs. In addition, more-deformable cells were found to roll with shear-independent velocities in vitro [169]. Those findings have provided motivation to consider mechanical properties as a possible biomarker for cancer cell stemness.…”
Section: The Seed the Journey And The Soil: The Metastatic Cascadementioning
confidence: 99%